ONLINE DOCTOR CONSULTATION (TELEMEDICINE) ON COVID-19 PATIENTS IN PERSPECTIVE DOCTOR'S RIGHTS PROTECTION - Kartina Pakpahan; Juli Esther Napitupulu; Dessy Darmayani Harianja (International Journal of Latin Notary, 2021)
In general, everyone has the right to health, so this means that the government must create conditions that allow each individual to live a healthy life, with efforts to provide adequate health care facilities and affordable health services for the community and the state is responsible for providing health care facilities. and proper public service facilities. In a pandemic condition like today, doctors as health care providers must still provide health care services to patients with the aim of improving patient health. The risk of transmitting the corona virus to each other between doctors and patients in health care facilities and the incessant calls for social and physical restrictions have made telemedicine a popular choice for both doctors and patients. Telemedicine is the provision of health services remotely by health professionals using information and communication technology, including the exchange of information on diagnosis, treatment, disease and injury prevention, research and evaluation, and continuing education of health care providers for the benefit of improving individual and community health. This study was conducted with the aim of knowing the mechanisms carried out by doctors or health workers for COVID-19 patients and the rights of doctors to protect in telemedicine services for Covid- 19 patients. The research method used in this study is library research, which is a method used by studying literature books, legislation. The analytical method used is qualitative analysis with descriptive analysis method, namely the selection of theories, principles, norms, doctrines, and articles in the most important legislation relevant to the problem. Then make a systematic from these data so that it will produce a certain classification. This study shows that Telemedicine carried out by doctors or other health workers on Covid-19 patients has been regulated in Article 17 paragraphs (1) and (2) and Article 18 paragraphs (1) and (2) of the Minister of Health 20/2019, but there is no synchronization of regulations regarding theprotection of doctors' rights in telemedicine services for Covid-19 patients in Indonesia, in this case receiving a service fee.